New Directions in Site Performance Practice: Intersecting Methodologies in an Era of Climate Coloniality - Kloetzel, Melanie (Performance Matters)

(untitled) (Institute for Performance Studies, Simon Fraser University, 2023)
In this short piece, I start to tease out the challenges of examining a field of performance that, in theory, deeply understands place but has insufficiently faced the impacts of climate coloniality on place, in part due to the fact that the field has largely been defined and developed by white researchers in the Global North. Specifically, by looking at a recent project called VINES, initiated by me and Brandy Leary, I dig into the site performance field’s investment in workshop-oriented practice-based research to consider what it might mean to intersect posthumanist research methodologies with Indigenous methodologies that emphasize relationality, reciprocity, and accountability.